Forty years on: a new national study of hearing in England and implications for global hearing health policy. (3rd January 2023) - Tsimpida, Dialechti; Panagioti, Maria; Kontopantelis, Evangelos
Abstract: Objective: We aimed to update the prevalence estimates of hearing loss in older adults in England using a nationally representative sample of adults aged 50 years old and older. Design: A comparative cross-sectional study design was implemented. Hearing loss was defined as ≥35 dB HL at 3.0 kHz, as measured via Hearcheck in the better-hearing ear. Study sample: We compared the estimates based on the English census in 2015 to estimates from psychoacoustic hearing data available for 8, 263 participants in the English Longitudinal Study of Ageing (ELSA) Wave 7 (2014–2015). Results: Marked regional variability in hearing loss prevalence was revealed among participants with similar age profiles. The regional differences in hearing outcomes reached up to 13.53% in those belonging to the 71–80 years old group; the prevalence of hearing loss was 49.22% in the North East of England (95%CI 48.0–50.4), versus 35.69% in the South East (95%CI 34.8–36.50). Conclusion: A socio-spatial approach in planning sustainable models of hearing care based on the actual populations' needs and not on age demographics might offer a viable opportunity for healthier lives. Regular assessment of the extent and causality of the population's different audiological needs within the country is strongly supported.